Online Anti-Rape Activism Exploring the Politics of the Personal in the Age of Digital Media - Loney-Howes, Rachel (Emerald Publishing, 2020)
Online Anti-Rape Activism examines the nature, use and scope of online spaces for anti-rape activism. Drawing on semi-structured interviews with activists from around the world, survey data from participants in these spaces, and a content analysis of social media pages, weblogs and websites, this book explores the complexities, contradictions, possibilities and politics that underscore the ways these online spaces are engaged with, regulated and their potential to contribute to social change.In the wake of the #MeToo movement, this book offers a critical commentary on the limitations and potentials of online anti-rape campaigning. It provides a foundation for understanding the emergence of #MeToo and sheds light on the complex history associated with keeping rape on the public agenda and the enduring tension between the personal and the political within feminist activism.The interdisciplinary and international approach makes this book suitable for a broad audience, including academics, students and activists working in the fields of gender and women's studies, media studies, politics, sociology and criminology worldwide.